Slang king M.E.S. on stage 1977-2013 - Smith, Mark E. 1957-2018 (At Last Books, 2021)
‘Slang King’ brings together nearly 40 years of Mark E Smith on stage with The Fall. From the start he warned us, We are Northern white crap that talks back, and he would rarely disappoint. This compilation of his intros—Good evening, we are the British Royal Navy and this is the art ass bandit section—outros—Thank you for allowing us in your … security area. We’re off to civilization. Good night—socio-political commentary, his heckling of the audience, holding other bands up to ridicule, and berating his own, the joking (always at someone’s expense), all a reminder of the degree to which he performed and wrote in real time, live. For Smith, content, and to a large degree discontent, was at the heart of it all, words and lyrics its very expression. His brain: his instrument. The steady, at times brave backing of the mighty Fall, his anchor and his launching pad. From the long, long days. Edited and with an introduction by critic and curator Bob Nickas, a Fall fan of rare vintage (first show: December 1, 1979, opening for the Buzzcocks at the Palladium in New York), the book is accompanied by more than 30 of Nikholis Planck’s drawings, created especially for publication herein.
Enthält Erinnerungen und Aufzeichnungen des Bandleaders Mark E. Smith
Keywords: Smith, Mark E. -- 1957-2018; Fall -- Musikgruppe; Geschichte 1977-2013